Differences of nucleotide and amino acid sequences of nucleoprotein (N) gene between wild-type measles virus and vaccine virus in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera Ibrahim; Agus Suwandono (Indonesian Pediatric Society, 2008)
Background Measles virus is a member of genus morbiliviruswhich belongs to family paramyxovirus with negative, single-strand RNA genome. RNA is packed by nucleocapsid (N) protein.The N protein is very important for RNA replication andtranslation. Abnormality in N protein will induce abnormality invirus replication.Objective This study aimed to explore the differences ofnucleotide sequence of N gene and amino acid sequences of Nprotein between wild-type measles virus (G2, G3 and D9) andvaccine virus (CAM-70, Schwarz and Edmonston-wt)Methods The exctraction and amplification of the gene wereconducted in the laboratory using biomolecular technology. Thegene and protein analysis were conducted using the bioinformatictechnology.Results The results showed that more differences were foundbetween nucleotide sequences of N gene of wild-type measlesvirus against CAM-70 vaccine virus (77 – 79 nucleotides)compared against Schwarz and Edmonston-wt vaccine virus (71-74 nucleotides). Likewise, more differences were also observedbetween amino acid sequences of N protein of wild-type measlesvirus against CAM-70 vaccine virus (18-24 residues) comparedagainst Schwarz and Edmonston-wt vaccine virus (17-23 residues).